Constrained Experimental Designs Part I: Construction of Projection Designs - Box, George; Hau, Ian (My University, 1990)
Experimental design is a powerful tool for quality improvement. In some situations, however, the design variables are subject to multiple linear constraints. In this report, we propose a class called projection designs which can be used when the design variables are constrained by linear relations. Fundamental issues such as region of interest and scaling of design variables are discussed. Then the construction of projection designs are illustrated.